1989
DOI: 10.1002/hep.1840100107
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the effects of interferon on chronic hepatitis B and the induction of 2′, 5′- oligoadenylate synthetase

Abstract: Two years or more after 35 patients (29 men and six women) with chronic hepatitis B were treated by interferon, we studied relationships of age, ALT activity, activity of serum DNA polymerase associated with the hepatitis B virus, serum levels of hepatitis B e antigen and activity of 2',5'-oligoadenylate synthetase in peripheral blood mononuclear cells when treatment started in comparison with treatment results. Seventeen patients were given human lymphoblastoid interferon-alpha; the other 18 patients were giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This result, together with previous studies, suggests that the HBc protein might modulate the expression of genes implicated in the antiviral and\or antiproliferative activity of IFN. This would fit with the in vivo and in vitro reciprocal interaction between IFN and HBV, as described previously (Ikeda et al, 1986 ;Jakschies et al, 1993 ;Nishiguchi et al, 1989 ;Onji et al, 1989 ;Poitrine et al, 1985). Our results are also consistent with our previous in vivo observations that suggest a role for dHBV DNA in the mechanism of HBV persistence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result, together with previous studies, suggests that the HBc protein might modulate the expression of genes implicated in the antiviral and\or antiproliferative activity of IFN. This would fit with the in vivo and in vitro reciprocal interaction between IFN and HBV, as described previously (Ikeda et al, 1986 ;Jakschies et al, 1993 ;Nishiguchi et al, 1989 ;Onji et al, 1989 ;Poitrine et al, 1985). Our results are also consistent with our previous in vivo observations that suggest a role for dHBV DNA in the mechanism of HBV persistence.…”
Section: Discussionsupporting
confidence: 93%
“…However, after IFN treatment, only about 30-40 % of patients show clearance of HBV replication markers, normalization of transaminases and improvement in liver histology (Perrillo et al, 1990). Several in vivo studies have shown a lack of activation of the IFN system in patients with acute or chronic hepatitis B (Ikeda et al, 1986 ;Jakschies et al, 1993 ;Nishiguchi et al, 1989 ;Poitrine et al, 1985). In addition, previous in vitro studies have suggested that HBV DNA might play a direct role in the development of resistance to endogenous or exogenous IFN.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HBsAg positive chronic active hepatitis show low levels of 2-5 OAS both in peripheral blood mononuclear cells and in serum, suggesting the possibility that the chronicity of HBV infection is related to a lack of activation in the endogenous interferon system (23,24). Whether chronic HCV infection by itself induces 2-5 OAS activity, remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn activates RNase to lyse virally derived RNA, thus inhibiting viral protein synthesis and suppressing the virus. (12)(13)(14) 29 ,59 -OAS activity in PBMC or serum has been used as an indicator that antiviral levels of rHuIFN-a have been achieved in vivo. (15,16) However, 29 ,59 -OAS activity levels in the liver, the target organ for treatments against chronic hepatitis B and C, have not been reported because of difficulties in evaluation.…”
Section: Introduction R Ec O M B In a N T H U M A N In Ter Fe Ro N -Amentioning
confidence: 99%